Pemanfaatan Big Data dalam Peningkatan Efektivitas Strategi Komunikasi Marketing Terpadu pada Perusahaan E-Commerce - Damayari Syira, Syahdina; Fauzi, Achmad; Woestho, Choiroel; Vilani, Laurencia; Firmansyah, Prado Dian; Pratama, Demas Rizky; Apriliana, Atun Dwi; Ghaffar, Naufal Shafly Abdul; Putri, Dhea Amelia (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This study aims to review the role of Big Data in marketing communication strategies in E-Commerce companies and what strategies companies use in developing their business by relying on Big Data. The method used in this research is qualitative, the material collected is in the form of words, and pictures, not numbers, meaning that the research results are made as is or by the actual situation. The results of this study indicate that the existence of Big Data in developing marketing communication strategies has a positive impact on both consumers and companies.